PENGARUH PENGGUNAAN VARIASI BERAT ROLLER TERHADAP PERFORMA SEPEDA MOTOR MATIC HONDA STLYO 160 - Rizal Santoso; Yuyun Estriyanto; Towip Towip (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2024)
This study aims to analyze the effect of roller weight variations on the performance of the Honda Stylo 160 automatic motorcycle in 2024. The research method used is a quantitative experiment with roller weight variations of 13, 15, 17, 19, and 20 grams. Tests were carried out using a dynamometer to measure torque and power. The results showed that the roller weight variation had a significant effect on the torque and power produced. The roller weighing 13 grams produced the highest torque of 23.55 N.m and power of 13.6 HP, while the heaviest roller of 20 grams produced the highest average power of 13.06 HP. The results of this study can be concluded that the use of lighter weight rollers tends to increase torque, while heavier weight rollers tend to increase the power generated. Although there is a general increase in power with an increase in roller weight, variations in the measurement results indicate that other factors such as engine efficiency also play an important role in motorcycle performance.